KERAGAAN PRODUKSI DAN HASIL BEBERAPA VARIETAS UNGGUL BARU (VUB) PADA SL PTT DI KABUPATEN KUANSING - Emi Sari Ritonga; Rathi Frima Zona (DINAMIKA PERTANIAN, 2014)
Demand for rice tends to increase every year, while the increasing of production of food crops and horticulture are not comparable with the pace of population growth that has not sufficient for the needs of the population, especially for rice. Therefore, the government has attempted to improve production through intensification and intensification programs and the development of the new high yielding varieties. For example, the district government of Kuantan Singingi which has a high potential of agriculture was done dissemination plot of VUB (Inpari 1, Inpari 6 jete, Inpara 1, Air Tenggulang, and Gilirang) in five sub-districts (Kuantan Tengah, Kuantan Mudik, Benai, Kuantan Hilir, and Gunung Toar). The assessment was conducted in Kuantan Singingi district on July to September 2010. The results showed that Inpari 1, Inpari 6 Jete, Inpara 1, Gilirang, Air Tenggulang varieties 7.0, 6.75 , 6.0, 5.9, 5 ton/ ha in production, respectively. The Inpari 1 and Inpari 6 varieties are the highest production than production of other varieties. Both varieties were appropriate to be developed in Kuantan Singingi District.